Central blood pressure for the management of hypertension: Is it a practical clinical tool in current practice?. Issue 3 (16th December 2019) - Cheng, Hao‐Min; Chuang, Shao‐Yuan; Wang, Tzung‐Dau; Kario, Kazuomi; Buranakitjaroen, Peera; Chia, Yook‐Chin; Divinagracia, Romeo; Hoshide, Satoshi; Minh, Huynh Van; Nailes, Jennifer; Park, Sungha; Shin, Jinho; et al.
Abstract: Since noninvasive central blood pressure (BP) measuring devices are readily available, central BP has gained growing attention regarding its clinical application in the management of hypertension. The disagreement between central and peripheral BP has long been recognized. Some previous studies showed that noninvasive central BP may be better than the conventional brachial BP in association with target organ damages and long‐term cardiovascular outcomes. Recent studies further suggest that the central BP strategy for confirming a diagnosis of hypertension may be more cost‐effective than the conventional strategy, and guidance of hypertension management with central BP may result in less use of medications to achieve BP control. Despite the use of central BP being promising, more randomized controlled studies comparing central BP‐guided therapeutic strategies with conventional care for cardiovascular events reduction are required because noninvasive central and brachial BP measures are conveniently available. In this brief review, the rationale supporting the utility of central BP in clinical practice and relating challenges are summarized.